The preliminary stretching effect on mechanical properties of natural and synthetic polyamide fibres and conformational transitions - Aksakal, Baki; Phoshkina, Svetlana P.; Darvish, Diana M.; Tsobkallo, Ekaterina S.; Alekberov, Vilayet (AMER INST PHYSICS, 2007)
The preliminary stretching effect on mechanical properties of natural (wool, hair, and silk) and synthetic polyamide fibres (nylon, capron) and conformational transitions are investigated by using a tensile tester. It is shown that alpha-keratin fibres (wool and hair) show silk-like properties and properties of synthetic polyamide fibres for preliminary extension of 18-24% and 34-38%, respectively.
Keywords: wool fibre; silk yarn; nylon; capron; alpha-helix; beta-sheet; alpha-keratin; preliminary stretching; alpha-beta transition; Physics